2022
DOI: 10.3389/fimmu.2022.919110
|View full text |Cite
|
Sign up to set email alerts
|

The KIR2DL2/HLA-C1C1 Gene Pairing Is Associated With an Increased Risk of SARS-CoV-2 Infection

Abstract: SARS-CoV-2 is the causative agent for the global COVID-19 pandemic; however, the interaction between virus and host is not well characterized. Natural killer cells play a key role in the early phase of the antiviral response, and their primary functions are dependent on signaling through the killer cell immunoglobulin-like receptor (KIR). This study measured the association between KIR/HLA class I ligand pairings and the occurrence and development of COVID-19. DNA of blood samples from 257 COVID-19 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Recent study revealed that the incidence of COVID-19 infection was higher in geographic regions with a high frequency of KIR2DL2. 32 Also, data suggest that KIR2DL2 gene to be a relevant factor favoring NK inhibition in endometriosis in Euro-descendants, contributing to the defective NK cytotoxic activity and impaired clearance of ectopic endometrial cells in the disease. 33 Additionally, comparatively higher frequencies of the KIR2DL5, KIR2DS2, and KIR2DS3 genes and lower frequencies of the KIR2DL1 and KIR2DL3 genes were seen in the Brazilian population compared to the Chinese population.…”
Section: Resultsmentioning
confidence: 99%
“…Recent study revealed that the incidence of COVID-19 infection was higher in geographic regions with a high frequency of KIR2DL2. 32 Also, data suggest that KIR2DL2 gene to be a relevant factor favoring NK inhibition in endometriosis in Euro-descendants, contributing to the defective NK cytotoxic activity and impaired clearance of ectopic endometrial cells in the disease. 33 Additionally, comparatively higher frequencies of the KIR2DL5, KIR2DS2, and KIR2DS3 genes and lower frequencies of the KIR2DL1 and KIR2DL3 genes were seen in the Brazilian population compared to the Chinese population.…”
Section: Resultsmentioning
confidence: 99%
“…A recent COVID-19 study suggested that KIR2DL2/HLA-C1C1 gene pairs could be a risk factor for SARS-CoV-2 infection [ 67 ]. When comparing 158 mild COVID-19 patients, 99 severely ill patients, and 98 healthy controls, KIR2DL2, KIR2DS3, HLA-C1C1, and KIR2DL2/HLA-C1 pairing frequencies were significantly higher in the COVID-19 patients than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the protective effect of KIR2DL3 on SARS-CoV-2 infection is associated with the absence of the KIR2DL2 gene. No correlation was found between the frequency of these genes and the outbreak of COVID-19 [ 67 ]. In this study, clusters of KIR2DL1/2/3 and 2DS1/2 genes also showed an independent association with HLA-C alleles ( Table S5 ).…”
Section: Discussionmentioning
confidence: 99%